An Investigation of the Efficacy of Cuttlefish Bone Powder in the Removal of Reactive Blue 19 Dye from Aqueous Solutions: Equilibrium and Isotherm Studies - Mohammad Taghi Ghaneian; Mojtaba Momtaz; Mahboobeh Dehvari (Shahid Sadoughi University of Medical Sciences, 2012)
Introduction: Discharge of textile wastewater causes the reduction of sunlight penetration, interferes with the receiving waters ecology and damage the environment. The aim of this study was to determine the removal efficiency of reactive blue 19 dye from aqueous solutions by cuttlefish bone powder. Materials & Methods: This study was performed experimentally and in laboratory scale. In this research, the effect of adsorbent dose, contact time, initial dye concentration and pH was evaluated. Dye concentration in unknown samples was determined by UV/Vis spectrophotometer. In order to better understand the adsorption process, the experimental data were analysed with Langmuir and Freundlich isotherm models. Results: Results showed that increasing the adsorbent dose up to 0.4 gr/100ml and increasing of contact time, led to an increase in the efficiency of dye removal. Increasing the initial pH had no effect on the adsorption efficiency and increasing the initial concentration of dye decreased the removal efficiency. The Removal efficacy of the dye was found to be 60%, 45%, 37.5% and 31.9% at the time interval of 3h and the initial dye concentrations of 25, 50, 75 and 100 mg/l, respectively. The experimental data were in good concordance with Langmuir isotherm model (R2=0.993). Conclusion: Cuttlefish bone powder is a natural and inexpensive adsorbent that can be used for the removal of environmental contaminations. The adsorption process is affected by sorbent dose, initial dye concentration and contact time but pH had no significant effect on removal efficiency